6- Steve Biko and Stoned Cherrie: Refashioning the Body Politic in Democratic South Africa - Vincent, Louise (African Sociological Review, 2007)
Steve Biko was a well-known hero and martyr of the anti-apartheid movement in South Africa. Detained, tortured and ultimately murdered in detention by the security police in 1977, he became a symbol of resistance in the mass mobilisations against apartheid that characterised the 1980s. His face appeared on the t-shirts of activists at rallies and funerals of others killed at the hands of the state. In contemporary, democratic South Africa, the politics of protest has given way to a new dynamic of black economic empowerment, the rise of a new black middle class and, with these, expressions of confident middleclass black individuality. The mass character of politics prior to 1994 has given way to the more prosaic forms associated with a constitutional democracy. But there have also been ways in which these two tropes have melded. The present article examines the use of Steve Biko’s image in post-apartheid South Africa byhome-grown design label Stoned Cherrie on its high fashion t-shirts and asks how we are to read this gesture.